MATH SOLVE

3 months ago

Q:
# What are the solutions of this system of equations?The first three steps in determining the solution set of thesystem of equations algebraically are shown.y = x2 - x-3y=-3x + 5(-2, -1) and (4, 17)(-2, 11) and (4, -7)(2, -1) and (-4, 17)(2, 11) and (-4,-7)Step12Equationx– X-3 = -3x +50 = x² + 2x - 80 = (x-2)(x+4)3

Accepted Solution

A:

Answer:Option C is correct.Step-by-step explanation:y = x^2-x-3 eq(1)y = -3x + 5 eq(2)We can solve by substituting the value of y in eq(2) in the eq(1)-3x+5 = x^2-x-3x^2-x+3x-3-5=0x^2+2x-8=0Now factorizing the above equationx^2+4x-2x-8=0x(x+4)-2(x+4)=0(x-2)(x+4)=0(x-2)=0 and (x+4)=0x=2 and x=-4Now finding the value of y by placing value of x in the above eq(2)put x =2y = -3x + 5y = -3(2) + 5y = -6+5y = -1Now, put x = -4y = -3x + 5y = -3(-4) + 5y = 12+5y =17so, when x=2, y =-1 and x=-4 y=17(2,-1) and (-4,17) is the solution.So, Option C is correct.